2003
DOI: 10.1074/jbc.m209706200
|View full text |Cite
|
Sign up to set email alerts
|

A G Protein-coupled Receptor Responsive to Bile Acids

Abstract: So far some nuclear receptors for bile acids have been identified. However, no cell surface receptor for bile acids has yet been reported. We found that a novel G protein-coupled receptor, TGR5, is responsive to bile acids as a cell-surface receptor. Bile acids specifically induced receptor internalization, the activation of extracellular signal-regulated kinase mitogen-activated protein kinase, the increase of guanosine 5-O-3-thiotriphosphate binding in membrane fractions, and intracellular cAMP production in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
1,436
6
17

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,373 publications
(1,502 citation statements)
references
References 26 publications
43
1,436
6
17
Order By: Relevance
“…5 Through activation of these 2 receptors, bile acids regulate their own synthesis, conjugation, transport and detoxification, as well as lipid, glucose, and energy homeostasis. 6 Furthermore, bile acids play an important role in maintaining intestinal barrier function, as antimicrobial agents that help determine the gut microbiome structure, and as inducers of genes encoding anti-microbial peptides and lectins via FXR.…”
Section: Introductionmentioning
confidence: 99%
“…5 Through activation of these 2 receptors, bile acids regulate their own synthesis, conjugation, transport and detoxification, as well as lipid, glucose, and energy homeostasis. 6 Furthermore, bile acids play an important role in maintaining intestinal barrier function, as antimicrobial agents that help determine the gut microbiome structure, and as inducers of genes encoding anti-microbial peptides and lectins via FXR.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, FXR activation by natural and synthetic and steroidal and nonsteroidal, ligands represses the expression of a set of TLR-4 regulated genes, including proinflammatory cytokines, chemokines, and their receptors. Because these counterregulatory effects are lost in FXR Ϫ/Ϫ macrophages, they selectively depend on FXR expression and are not mediated by other receptors, such as the recently discovered G protein-coupled receptor TGR5, a seven-trans-membrane domain receptor for bile acids that is also expressed in macrophages (29). Furthermore, the preventive effect of INT-747 was lost in FXR Ϫ/Ϫ mice (supplemental Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, it was found that human pulmonary macrophages possess a bile acid-specific Gprotein receptor known as TGR5 that, to an unknown extent, sequesters bile acid. [12] At present, investigations have not identified rat pulmonary macrophages as possessing either a TGR5 receptor analog [12,13] or other receptors for binding bile or trypsin. Thus, it may be that clearance of bile and trypsin from the lung is not the result of receptor-mediated processes carried out by rat pulmonary macrophages.…”
Section: Discussionmentioning
confidence: 99%